2013
DOI: 10.1371/journal.pone.0056595
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor NR4A2 Orchestrates Th17 Cell-Mediated Autoimmune Inflammation via IL-21 Signalling

Abstract: IL-17-producing CD4+ T helper 17 (Th17) cells are pathogenic in a range of human autoimmune diseases and corresponding animal models. We now demonstrate that such T cells infiltrating the target organ during the induction of experimental autoimmune encephalomyelitis (EAE) and experimental autoimmune uveoretinitis (EAU) specifically express NR4A2. Further, we reveal a critical involvement of NR4A2 in Th17 cell functions and Th17 cell-driven autoimmune diseases. When NR4A2 expression was blocked with siRNA, full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 53 publications
5
72
1
Order By: Relevance
“…NR4A2 was also seen to direct the development of both Treg (Sekiya et al, 2013) and Th17 (Raveney et al, 2013) cells, resulting respectively in the protection and exacerbation of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NR4A2 was also seen to direct the development of both Treg (Sekiya et al, 2013) and Th17 (Raveney et al, 2013) cells, resulting respectively in the protection and exacerbation of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, it has been demonstrated that NR4A2 is involved in controlling the transcription of NF-κB target genes (Saijo et al, 2009), and in the development of Treg cells (Sekiya et al, 2011 andSekiya et al, 2013); its low expression has been correlated with MS , Achiron et al, 2010. On the other hand, it has been shown to have a role in the differentiation of Th17 cells (Raveney et al, 2013) and to be overexpressed in a population of Japanese MS patients (Satoh et al, 2005).…”
mentioning
confidence: 99%
“…NR4A2 also influences maturation and differentiation of Th17 T-cells and may thereby have a role in both autoimmunity and in resolution of infections [160]. NR4A2, but not NR4A1 or NR4A3, is upregulated in rheumatoid arthritis, where its expression is induced by PGE2, IL-1β, and TNF-α [161], suggesting that this factor may have broad effects in limiting inflammatory responses through its function as a transrepressor of the NFκB pathway.…”
Section: Nr4a2 In Cellular Homeostasis and Diseasementioning
confidence: 99%
“…87 The genetic ablation of Nr4a2 in CD41 T cells resulted in a failure to induce Th17 differentiation in vitro. Similarly, siRNA-mediated gene silencing of Nr4a2 in T cells ameliorated pathogenesis in murine EAE.…”
Section: Aryl Hydrocarbon Receptor (Ahr)mentioning
confidence: 99%